Quantitative study on GHG emissions and the GWP influence of cemetery green space maintenance based on LCA - Liu, Yang; Lei, Yakai; Johnston, Douglas M.; Jiang, Mingyu; Dong, Nalin; Xie, Dongbo; Ma, Zitong; Zhang, Xinyu; Guo, Nan (Journal of Environmental Engineering and Landscape Management, 2023)
Cemetery landscapes are austere and generally require maintenance. The materials and equipment used for maintenance emit greenhouse gases (GHGs). This research aimed to quantify the annual GHG emissions and global warming potential (GWP) indices of traditional and natural cemeteries for more environmentally friendly green and grey facility planning of cemetery areas. Based on life cycle assessment (LCA), in Yorkshire, UK, as an example, traditional cemeteries were found to be mostly established with landscaped cemetery facilities, and natural cemeteries were found to include mostly underground burials covered with wild plants. The average GHG emissions per hm2 in traditional cemetery maintenance (1,552.88 kg/CO2-e) were 1.8 times those in natural cemeteries (870.88 kg/CO2-e). In the cemetery plant community, the mean GHG emissions for grassland maintenance (1,867.65 kg/CO2-e) were 6.7, 2.8 and 2.3 times higher than the woodland, meadow and shrub maintenance values of 280.77, 673.03 and 821.00 kg/CO2-e, respectively. The mean GWP indexes for traditional and natural cemetery green space maintenance were 0.027 and 0.015, respectively, which were generally higher than those for urban green space maintenance (0.010). This research recommends replacing grasslands with wild meadows, reducing the size of ground cemetery facilities and limiting the application of maintenance materials (i.e., irrigation water and pesticides) to reduce the environmental impact of green space in cemeteries.